(8m-8m-27)(8m-25m-14)=0

Simple and best practice solution for (8m-8m-27)(8m-25m-14)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (8m-8m-27)(8m-25m-14)=0 equation:


Simplifying
(8m + -8m + -27)(8m + -25m + -14) = 0

Reorder the terms:
(-27 + 8m + -8m)(8m + -25m + -14) = 0

Combine like terms: 8m + -8m = 0
(-27 + 0)(8m + -25m + -14) = 0
(-27)(8m + -25m + -14) = 0

Reorder the terms:
-27(-14 + 8m + -25m) = 0

Combine like terms: 8m + -25m = -17m
-27(-14 + -17m) = 0
(-14 * -27 + -17m * -27) = 0
(378 + 459m) = 0

Solving
378 + 459m = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-378' to each side of the equation.
378 + -378 + 459m = 0 + -378

Combine like terms: 378 + -378 = 0
0 + 459m = 0 + -378
459m = 0 + -378

Combine like terms: 0 + -378 = -378
459m = -378

Divide each side by '459'.
m = -0.8235294118

Simplifying
m = -0.8235294118

See similar equations:

| .3(y)+.14(x)=.18 | | x+4x=58 | | -(3/5)x=(2/5) | | F(9)=100x-5 | | 5x/6-y/3=6 | | 19m=40-17.95 | | 36m^2-49/16=0 | | 37=-2(22-X)+3(X-3) | | (9-3x)(9-5x)= | | -11x^2+3x+11=0 | | 382=x+(x+6) | | (4/11)x=28 | | 3x-108=0 | | 7k-4k=12 | | x+.7=-.2 | | 3x=2(2x-3) | | k/2+5=8 | | s-32=-48 | | v+(v-30.8)+(v+27.3)=202.9 | | 3x^3-7x^2+6x-2=0 | | y^2+2x+8y+13=0 | | 12x^2-24-9=0 | | -7/9x23/4 | | x+(x+6)=382 | | x=-9/2-5/3 | | 4.2/-0.15 | | x-7.7=-3.5 | | -9/2-5/3 | | -11x^2+20x=0 | | 3x^3-7x^2=2-6x | | -27/12/-1/6 | | x-50=32 |

Equations solver categories